A "people dump": Marks of suffering and transformations at the former Hospital Colônia Sant'Ana and in psychiatric care in Santa Catarina, 1970-1996 Um "depósito de gente": As marcas do sofrimento e as transformações no antigo hospital Colônia Sant'Ana e na assistência psiquiátrica em Santa Catarina, 1970-1996 - Borges V.T.* (2013)
The article explores transformations to psychiatric care in Santa Catarina starting in the 1970s, when the state's longtime asylum, Hospital Colônia Sant'Ana, reached the height of overcrowding. To this end, along with other sources, it analyzes interviews that had been conducted with professionals who worked at the hospital in that era, sourced from the facility's Center for Documentation and Research. The goal was to problematize these testimonies, examining the texture of the accounts and approaching them as memories that weave a history of the hospital through recollections marked by suffering. Within this proposed framework, suffering is understood as a historical event that can give rise to new social arrangements.